Euroisation in Albania: From Spontaneous to Consensual - Erjon Luci; Marta Muco; Elvira Sojli (The Vienna Institute for International Economic Studies (wiiw), 2006)
In this paper, we present a new estimation of the euroisation level of the Albanian economy taking into account both foreign deposits and foreign currency in circulation. We implement a recent novel methodology to calculate foreign currency in circulation. It is found that the overall level of euroisation including this often unaccounted measure is approximately 45 percent of total money. We also try to investigate some of the implications the re-estimated level of euroisation has on the actual monetary policy and the future path towards EMU.
Keywords: 330; euroisation; foreign currency in circulation; Albania